UNSUR INTRINSIK DAN EKSTRINSIK DALAM FILM “JOKOWI” - muhamad ramdan (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Film is a literary work that is audiovisual, can bring up a picture, image of motion along with sound recorded through the media, so that it has a narrative meaning that is understood by the audience. Film is considered as a very effective learning communication medium for all ages, both for the community and students. This research is based because many films are not suitable to be watched, especially for students, so that research is needed as a measure of eligibility for a film. One of the interesting films to study is the film "Jokowi" by director Azhar Kinoi Lubis on the grounds that this film is watched in many Indonesian cinemas. The formulation of the problem to be investigated is the intrinsic and extrinsic elements contained in the Jokowi film. This study aims to get an overview of the intrinsic and extrinsic elements contained in the Jokowi film so that it can draw conclusions about the feasibility of this film. Researchers used a qualitative descriptive method by telling the conclusions of Jokowi's film, whether this film was appropriate or not watched by students